Transcranial Magnetic Stimulation for Long-Term Smoking Cessation: Preliminary Examination of Delay Discounting as a Therapeutic Target and the Effects of Intensity and Duration - Shevorykin, Alina; Carl, Ellen; Mahoney, Martin C.; Hanlon, Colleen A.; Liskiewicz, Amylynn; Rivard, Cheryl; Alberico, Ronald; Belal, Ahmed; Bensch, Lindsey; Vantucci, Darian; Thorner, Hannah; Marion, Matthew; et al. (Frontiers in Human Neuroscience, 2022)
Background Repetitive transcranial magnetic stimulation (rTMS) is a novel treatment for smoking cessation and delay discounting rate is novel therapeutic target. Research to determine optimal therapeutic targets and dosing parameters for long-term smoking cessation is needed. Due to potential biases and confounds introduced by the COVID-19 pandemic, we report preliminary results from an ongoing study among participants who reached study end prior to the pandemic. Methods In a 3 × 2 randomized factorial design, participants (n = 23) received 900 pulses of 20 Hz rTMS to the left dorsolateral prefrontal cortex (PFC) in one of three Durations (8, 12, or 16 days of stimulation) and two Intensities (1 or 2 sessions per day). We examined direction and magnitude of the effect sizes on latency to relapse, 6-month point-prevalence abstinence rates, research burden, and delay discounting rates. Results A large effect size was found for Duration and a medium for Intensity for latency to relapse. Increasing Duration increased the odds of abstinence 7–8-fold while increasing Intensity doubled the odds of abstinence. A large effect size was found for Duration, a small for Intensity for delay discounting rate. Increasing Duration and Intensity had a small effect on participant burden. Conclusion Findings provide preliminary support for delay discounting as a therapeutic target and for increasing Duration and Intensity to achieve larger effect sizes for long-term smoking cessation and will provide a pre-pandemic comparison for data collected during the pandemic. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT03865472].